Condominium design a correlational analysis between user satisfactions and physical designs - Puso, Mark Ndsy L. (2013)
We cannot deny the growth, improvement and industrialization of Davao City are undeniably a reality. The city has plenty of infrastructure projects coming from the government and from different private sectors. A large part of it is due to the investments being impacted by local, national, and even international companies. These large companies, if not all, contribute to most of the building infrastructures and the like. Thus, it is slowly and inevitably consuming the lands of Davao City, specifically the city center. From the statement above, the problem that is now arising is the lack of residential community in which there is satisfactory building that will cater the rising number of professionals, entrepreneurs, foreign students and other productive citizens that plays a big role on the development of Davao City. In addition to such problems is the lack of land area to build a housing community. This leads to a solution of building a Multi-storey residential Complex or Condominium. The condominium industry in Davao City is already introduced to Davao City but still in its fresh years. Its introduction to Davao City society plays a very critical role to the acceptance of the concept of condominium living specially that the Davaoenos tends to display characters that reflect their purchasing power behavior. If the condominium industry succeeds, it will facilitate in catering or providing a healthy residence for urban population and thus improving their productivity. In relation to such circumstance, this study was conducted to further explore the residential satisfaction of condominium users, and the dimensions (focused on architectural dimensions) which go to make up residential satisfaction. Also, this study will help determine if the satisfaction of the users and the profit of the developers are possible to exist at the same time. Hence, this study may lead to conclusion whether socialized multi-level housing and long term condominium and high satisfactory condominium is possible.